A cautionary tale on research methods in the field of parents - Pepe, Alessandro; Castelli, Stefano (International Journal about Parents in Education, 2023)
It is with great pleasure that we introduce the new volume (n.7, issue 1) of the International Journal about Parents in Education. During the last years, the journal has increased the number of submissions from a wider international audience who is continuously working on the topic of parents in education. Looking at bibliometric measures, the IJPE’s H-index (Hirsh, 2005) and Gindex (Egghe, 2006) are steady growing: this represents a quite satisfying result for a still young (and tenaciously open access) journal, situated in a very challenging and competitive context.